Adapting Systematic Literature Reviews for Undergraduate Thesis Projects: A Conceptual Framework - Muhammad Iqbal; M. Rasyid Ridlo; Agus Jayadi; Nuraeni Nuraeni (Pedagogia: Jurnal Ilmiah Pendidikan, 2026)
This article aims a explore conceptual analysis of authoritative SLR guidelines to develop the Undergraduate SLR Model - a simplified yet rigorous seven-stage framework specifically designed for undergraduate thesis projects. Systematic literature review (SLR) has gained increasing adoption in undergraduate educational research, yet most established SLR guidelines were developed for advanced research contexts and impose procedural demands that exceed undergraduate students' capacity in terms of time, database access, methodological training, and team composition. This study employed a conceptual research design through the systematic analysis and synthesis of authoritative SLR guidelines to identify essential methodological principles and adapt them to undergraduate research contexts. The results is unlike existing SLR guides that target graduate or professional researchers, this framework explicitly addresses the constraints of single-researcher settings by introducing supervisor validation as a quality assurance substitute for dual-reviewer screening, limiting database requirements to one primary source with a mandatory supplementary search strategy, and recommending thematic narrative synthesis as a feasible alternative to meta-analysis. The model also provides a decision guide for choosing between SLR and scoping review approaches, practical tools including a simplified PRISMA Flow Diagram and self-assessment checklist, and guidance for collaborative multi-researcher scenarios. This framework offers a methodological reference that enables undergraduate students and their supervisors to conduct literature reviews that are both rigorous in principle and realistic in practice.